Integrating Islamic Values into General Subjects in Elementary Schools: A Holistic Approach to Character Education - Hidayat, Syarip; Sutisna, Aang; Jaelani, Rusani (Papanda Publisher, 2025)
The integration of Islamic values into general subjects at the elementary level is increasingly recognized as a necessary approach to fostering balanced intellectual, moral, and spiritual development among students. This study aims to explore the role and implementation of such integration as a means of forming holistic character in young learners. This research adopts a literature review method, synthesizing data from scholarly books, journal articles, and research reports relevant to the integration of Islamic values in general education. The review focuses on theoretical concepts, previous empirical findings, implementation strategies, and current challenges. The findings reveal three key pillars essential to successful integration: (1) enhancing students' contextual understanding of Islamic values by linking them to relevant content in subjects such as Mathematics, Science, Social Studies, and Language; (2) fostering holistic character development by embedding ethical and spiritual dimensions into cognitive learning; and (3) identifying effective strategies to address implementation challenges, including teacher training, curriculum development, and the cultivation of a religious school culture. Despite barriers such as limited teacher capacity, insufficient instructional materials, and perceived curriculum overload, the integration of Islamic values has shown significant potential to close the gap between religious and secular education. Through targeted interventions—such as professional development, integrative textbooks, and community involvement—schools can create environments that promote ethical behavior, critical thinking, and spiritual awareness simultaneously. The study concludes that Islamic values integration in general subjects is not merely an educational enrichment, but a transformative strategy for shaping morally grounded and intellectually capable future generations.